A light-weight performance model for optical buffers. (15th October 2008) - Rogiest, W.; Fiems, D.; Laevens, K.; Bruneel, H.
Providing a photonic alternative to the current electronic switching in the backbone, optical burst switching (OBS) requires that also the buffering is implemented optically, with a set of fiber delay lines (FDLs). Previous performance studies pointed out that the resulting optical buffer suffers additional performance loss (when compared to RAM), but did not allow an exact quantification of this difference for general traffic assumptions. The optical buffer model we constructed considers general inter-arrival times and burst sizes, and is valid for general line lengths. Important features include exactness (no approximations) and minimal numerical complexity (light-weight). This document provides formulas for the waiting times and the loss performance. Also, performance graphs illustrate the paramount impact of correlation, that can be determined exactly and with minimal computational effort with the developed model.